Work life balance, leadership style and turnover intention among generation Y in Malaysia - Louis Marcus, William (2020)
The primary purpose of this study was to investigate the relationship of Work Life Balance and Transformational Leadership style towards turnover intention among Generation Y in Malaysia. Primary data was collected through distribution of 500 questionnaires to Generation Y respondent regardless of industries, position or type of job. A in total of 400 useable questionnaires were returned and are used for data analysis by using IBM Statistical Package for Social Science 25 version. The result of the study revealed a significant negative relationship between Work Life Balance and Turnover Intention. Transformational leadership is found negatively related to Turnover Intention. This study has revealed that as long Gen Y feel a balance between work and life, and they are under the supervision of transformational leadership, they are less likely to have the intention of quit.